Use of Web 2.0 tools by hospital pharmacists - B. Bonaga Serrano; R. Aldaz Francés; M. R. Garrigues Sebastiá; M. Hernández San Salvador (Elsevier, 2014)
Objective: Web 2.0 tools are transforming the pathways health professionals use to communicate among themselves and with their patients so this situation forces a change of mind to implement them. The aim of our study is to assess the state of knowledge of the main Web 2.0 applications and how are used in a sample of hospital pharmacists. Method: The study was carried out through an anonymous survey to all members of the Spanish Society of Hospital Pharmacy (SEFH) by means of a questionnaire sent by the Google Drive® application. After the 3-month study period was completed, collected data were compiled and then analyzed using SPPS v15.0. Results: The response rate was 7.3%, being 70.5% female and 76.3% specialists. The majority of respondents (54.2%) were aged 20 to 35. Pubmed was the main way of accessing published articles. 65.2% of pharmacists knew the term "Web 2.0". 45.3% pharmacists were Twitter users and over 58.9% mainly for professional purposes. Most pharmacists believed that Twitter was a good tool to interact with professionals and patients. 78.7% do not use an agregator, but when used, Google Reader was the most common. Conclusion: Although Web 2.0 applications are gaining mainstream popularity some health professionals may resist using them. In fact, more than a half of surveyed pharmacists referred a lack of knowledge about Web 2.0 tools. It would be positive for pharmacists to use them properly during their professional practice to get the best out of them.